Development of an optimization methodology for formulating both jet fuel and diesel fuel surrogates and their associated skeletal oxidation mechanisms. (1st November 2018) - Yu, Wenbin; Zhao, Feiyang; Yang, Wenming; Tay, Kunlin; Xu, Hongpeng
Highlights: An optimization methodology was developed for formulating fuel surrogates. New jet fuel and diesel fuel surrogates are formulated with same five components. New skeletal mechanisms of jet fuel and diesel fuel surrogates were developed. Sufficient model validations were conducted. Abstract: In this study, an optimization methodology was developed for formulating both jet fuel and diesel fuel surrogates along with their associated skeletal oxidation mechanisms. Based on this methodology, new jet fuel surrogate (JFS) and diesel fuel surrogate (DFS) are formulated with same five components (n-dodecane/ iso -octane/ iso -cetane/decalin/toluene) by emulating practical fuel properties including liquid density, viscosity, surface tension, cetane number (CN), hydrogen-carbon (H/C) ratio, molecular weight (MW), lower heating value (LHV) and threshold sooting index (TSI). Based on the newly developed JFS and DFS, their associated chemical skeletal mechanisms were developed, which are described with same chemical reaction structure: five skeletal sub-mechanisms are employed into the skeletal fuel mechanisms, including decalin (C10 H18 ), n-dodecane (C12 H26 ), iso -cetane (C16 H34 ), iso -octane (C8 H18 ) and toluene (C7 H8 ) sub-mechanisms. By describing the chemistries for the oxidation of large molecules C4-Cn and small H2/CO/C1 molecules respectively, the skeletal mechanisms are significantly compacted into 74 species and 189 reactions, which makes them practical to be used in 3-D engine combustion simulations. In addition to sufficient 0-D validations of ignition delay times, species concentrations and laminar flame speed in various environments, 3-D validations of constant volume spray and engine combustion were also performed for the new JFS and DFS skeletal mechanisms. It can be observed that the agreements between the computational results predicted by the present mechanisms and all the experimental data are reasonably good, which proves that the newly proposed JFS and DFS skeletal mechanisms are robust and accurate to be used in engine combustion computational fluid dynamics (CFD) studies.